Effect of the matrix system in the delivery and in vitro bioactivity of microencapsulated Oregano essential oil - Costa, Sara Beirão da (2012)
The effect of encapsulating matrix on retention, protection and delivery of Oregano essential oil (EO) was studied. EO was encapsulated in rice starch porous spheres, inulin and gelatine/sucrose capsules by spray drying. Gelatine/sucrose matrix was also dried by freeze drying. Experimental designs were applied to test the effect of bonding agents and solids content for rice starch and drying temperature and solids content for inulin and gelatine/sucrose systems. The ratio of gelatine/sucrose was also tested. EO was identified (confocal laser scanning microscopy and FT-IR) in all tested matrices and the release profiles,antioxidant activity and antimicrobial activity of encapsulates evaluated. Results showed that the three tested materials are able to encapsulate Oregano EO. Higher diffusion coefficients were obtained for starch microcapsules (about 1013 m2/s) followed by spray-dried gelatine/sucrose systems (about 1015 m2/s) and inulin microcapsules (about 1016 m2/s). Gelatine/sucrose microparticles exhibit high antioxidant and antimicrobial activity while inulin and rice starch microencapsulates ensure higher stability.